Analytical Geometry!

Algebra Level 5

Draw a tangent line of parabola y = x 2 y=x^2 at the point A ( 1 , 1 ) A(1,1) . Suppose the line intersects the x x -axis and y y -axis at D D and B B respectively. Let point C C be on the parabola and point E E on A C AC such that A E E C = λ 1 \dfrac{AE}{EC}=\lambda_{1} . Let point F F be on B C BC such that B F F C = λ 2 \dfrac{BF}{FC}=\lambda_{2} and λ 1 + λ 2 = 1 \lambda_{1}+\lambda_{2}=1 . Assume that C D CD intersects E F EF at point P P . When point C C moves along the parabola, the equation of the trail of P P can be expressed in the form 1 a ( m x + b ) 2 \dfrac{1}{a}(mx+b)^2 . Where g c d ( m , b ) = 1 gcd(m, b)=1 , find the value of a + b + m a+b+m .

  • This problem is not original.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sean Ty
Oct 26, 2014

We know that the equation of the tangent line passing through ( 1 , 1 ) (1,1) is y = 2 x 1 y=2x-1 . And D D is the midpoint of A B AB .

Let γ = C D C P , t 1 = C A C E = 1 + λ 1 , t 2 = C B C F = 1 + λ 2 \gamma=\dfrac{CD}{CP}, t_1=\dfrac{CA}{CE}=1+\lambda_{1}, t_2=\dfrac{CB}{CF}=1+\lambda_{2} . Then t 1 + t 2 = 3 t_1+t_2=3 .

We know that A D = A B 2 AD=\dfrac{AB}{2} , [ C A B ] = 2 [ C A D ] = 2 [ C B D ] [CAB]= 2[CAD]=2[CBD] . But we have 1 t 1 t 2 = ( C E ) ( C F ) ( C A ) ( C B ) = [ C E F ] [ C A B ] = [ C E P ] 2 [ C A D ] + [ C F P ] 2 [ C E D ] = 3 2 t 1 t 2 γ \dfrac{1}{t_1t_2}=\dfrac{(CE)(CF)}{(CA)(CB)}=\dfrac{[CEF]}{[CAB]}=\dfrac{[CEP]}{2[CAD]}+\dfrac{[CFP]}{2[CED]}=\dfrac{3}{2t_1t_2\gamma} .

Thus, γ = 3 2 \gamma=\dfrac{3}{2} . And P P is the centroid of A B C \triangle ABC .

Then consider the points P ( x , y ) P(x, y) and C ( x 0 , x 0 2 ) C(x_0, x_{0}^{2}) . Since C C is different from A A , x 0 1. x_0 \neq 1. And the coordinates of P P are ( 1 + x 0 3 , x 0 2 3 ) (\dfrac{1+x_0}{3}, \dfrac{x_{0}^{2}}{3}) . Keeping in mind that x 2 3 x \neq \dfrac{2}{3} . Eliminating x 0 , x_0, we obtain y = 1 3 ( 3 x 1 ) 2 y=\dfrac{1}{3}(3x-1)^2 . So the equation of the trail is y = 1 3 ( 3 x 1 ) 2 , x 2 3 y=\dfrac{1}{3}(3x-1)^2, x\neq \dfrac{2}{3} .

Therefore, the answer is 3 1 + 3 = 5 3-1+3=\boxed{5} .

Pranjal Jain
Oct 26, 2014

A DUMB SOLUTION

Just substitute C \equiv (-1,1) and (0,0) , λ 1 = 1 \lambda_{1}=1 and λ 2 = 0 \lambda_{2}=0 . You will get two constraints:

  • 3 b 2 = a 3b^{2}=a

  • m = 3 b m=-3b

Put m=3 (Its clear by 2 n d 2^{nd} constraint that m is a multiple of 3 to find out a and b.

The main step is to note that P is the centroid of triangle ABC. Then it would become quite straightforward from there.

Joel Tan - 6 years, 7 months ago

Log in to reply

Yes, there are two solutions. That one, and a bashy one.. :)

Sean Ty - 6 years, 7 months ago

Can you prove that it would be centroid of \triangle ABC

Pranjal Jain - 6 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...